Arboreal structure in primary forests of Picea martinezii T.F. Patterson - Treviño-Garza, Eduardo Javier; López Martínez, José Israel; Aguirre Calderón, Oscar Alberto; Mata Balderas, José Manuel (Acta Universitaria, 2023)
The influence of human activities on ecosystems has spread over almost the entire earth’s surface; however, there are still some with little or no activity that are considered primary. The objective was to characterize and compare the tree structure in four localities in old-growth mixed forests considered primary, with Picea martinezii as a dominating species. In those areas, a site of 2500 m2 was established, where dasometric information of all tree individuals was recorded and analyzed with structural indices such as Clark and Evans (R), species mixture (Mi), differentiation (Ti), and dimensional dominance (Ui). The general analysis indicated a random distribution (R close to 1), with a high degree of mixing (Mi = 0.75) and balanced differentiation and dimensional dominance (Ti and Ui values close to 0.50). It is concluded that the studied forests have similar and stable structural conditions.